2009
DOI: 10.1016/j.orl.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Certification of an optimal TSP tour through 85,900 cities

Abstract: a b s t r a c tWe describe a computer code and data that together certify the optimality of a solution to the 85,900-city traveling salesman problem pla85900, the largest instance in the TSPLIB collection of challenge problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 13 publications
0
75
0
2
Order By: Relevance
“…Several polynomial-time heuristic methods with upper bounds on performance have been proposed since to approximately solve the TSP, including nearest neighbor, nearest insertion, furthest insertion [42], Christofides heuristic [43], and LK heuristic (see [44] for a comprehensive overview of methods). Currently, the largest TSP instance solved to optimality comprises nearly 86,000 cities [45].…”
Section: Traveling Salesman Problem (Tsp)mentioning
confidence: 99%
“…Several polynomial-time heuristic methods with upper bounds on performance have been proposed since to approximately solve the TSP, including nearest neighbor, nearest insertion, furthest insertion [42], Christofides heuristic [43], and LK heuristic (see [44] for a comprehensive overview of methods). Currently, the largest TSP instance solved to optimality comprises nearly 86,000 cities [45].…”
Section: Traveling Salesman Problem (Tsp)mentioning
confidence: 99%
“…Helsgaun (Helsgaun 2009 andApplegate et al 2009) has developed extremely effective approaches for solving the traveling salesman problem with as many as 10,000,000 nodes and has demonstrated that his computationally efficient procedure has found a solution to these very large traveling saleman problems that is within .02% of the optimal solution.…”
Section: Traveling Salesman Problemmentioning
confidence: 99%
“…Despite important work in this problem, cutting plane techniques to date are still limited in terms of the instance sizes that can effectively be tackled computationally. This is a problem, because if there is any hope of being able to solve large integer programming formulations of PCKP generalizations, such as those that appear in the context of open pit mining, cutting planes are likely to play an important role as they have in solving other large combinatorial optimization problems [2,3].…”
Section: Introductionmentioning
confidence: 99%